Sliding Crosslinked Thermoresponsive Materials: Polypseudorotaxanes Made of Poly(N-Isopropylacrylamide) and Acrylamide-γ-Cyclodextrin - Malucelli, Giulio; Dore, Jvan; Sanna, Davide; Nuvoli, Daniele; Rassu, Mariella; Mariani, Alberto; Alzari, Valeria (Frontiers in Chemistry, 2018)
Novel polypseudorotaxanes based on poly(N-isopropylacrylamide) (PNIPAAm) and acrylamide-γ-cyclodextrin (AγCD) are successfully synthesized. AγCD gives rise to sliding crosslinking systems and influences the thermoresponsive and swelling behavior of PNIPAAm hydrogels. Namely, their lower critical solution temperature can be tuned up to 38 °C, thus making the resulting materials of great interest in biomedical applications. Also, AγCD influences the thermal and mechanical properties of hydrogels, by affecting the Tg and E modulus values.